Identification of a new hepatitis B virus (HBV) genotype from Brazil that expresses HBV surface antigen subtype adw4 - H. H. Naumann; Stephan Schaefer; Clara Fumiko Tachibana Yoshida; Ana Gaspar; Reinald Repp; Wolfram H. Gerlich (1993)
The complete genome of a hepatitis B virus (HBV) from Brazil that expressed the subtype adw4 of HBV surface antigen (HBsAg) was cloned and sequenced. The genome, termed w4B, consists of 3215 bp. The overall genetic organization of typical hepadnaviruses with four open reading frames including the preC region was found to be conserved. When comparing the w4B sequence with 19 complete HBV genomes it was, however, found to be more divergent (15%) than any other HBV sequence thus far reported. Until now, no more than 11% divergence has been reported. Distinct from the five known HBV genotypes A to E, w4B made up a new, sixth genotype. The importance of the conserved third start codon in the HBV X gene became apparent in isolate w4B. By mutation, this ATG was out of frame, and by what appears to have been a linked mutation, a new start site two codons downstream was re-established. The significance of several other mutations is discussed.